2007
DOI: 10.1111/j.1834-7819.2007.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pharmacological variables as a risk factor for nifedipine‐induced gingival overgrowth

Abstract: Background: Gingival enlargement is usually noted within one to two months after the initiation of nifedipine therapy. The aetiology of nifedipineinduced gingival overgrowth is uncertain. The aim of this study was to determine the relationship between plasma and gingival crevice fluid (GCF) nifedipine concentrations and the degree of gingival overgrowth in patients treated with nifedipine, and also to assess the correlations between clinical and pharmacological variables. Methods: Eighteen patients taking nife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Gingival inflammation is considered an important risk factor in the expression of GO correlated to nifedipine use [8]. The GI observed in the present study showed results similar to those reported by Barclay et al [5], King et al [9], Güncü et al [21], and Miranda et al [23]. PB results were similar to those reported by Tavassoli et al [17], whereas Margiotta et al [20] did not detect a correlation between PB and GO.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gingival inflammation is considered an important risk factor in the expression of GO correlated to nifedipine use [8]. The GI observed in the present study showed results similar to those reported by Barclay et al [5], King et al [9], Güncü et al [21], and Miranda et al [23]. PB results were similar to those reported by Tavassoli et al [17], whereas Margiotta et al [20] did not detect a correlation between PB and GO.…”
Section: Discussionsupporting
confidence: 91%
“…However, the Spearman test did not reveal a correlation between patients gender and the occurrence of GO, in agreement with data reported by King et al [9], Margiotta et al [20], and Güncü et al [21]. According to Seymour et al [8], there are evidences that male patients under treatment with nifedipine and cyclosporine are more prone to a greater prevalence and severity of GO than female patients [9, 20].…”
Section: Discussionsupporting
confidence: 87%
“…Different prevalence rates (20% to 50%) have been reported for GO induced by CCB[ 5 6 7 ] for nifedipine-induced GO, while a prevalence rate of 3.3%[ 8 ] was reported for amlodipine-induced GO. These, however, represent Caucasians’ values.…”
Section: Introductionmentioning
confidence: 99%
“…A stock solution of nifedipine, of 10 mg/mL, was prepared by dissolving 1 mg of nifedipine (Sigma‐Aldrich, St Louis, MO, USA) in 100 μL of dimethylsulfoxide (DMSO) (Amresco, Solon, OH, USA). Taking into account the nifedipine concentrations in the plasma and in the gingival crevicular fluid , we chose two concentrations of nifedipine – 0.2 and 20 μg/mL – for use in this study. The final concentration of solvent in the medium was 0.2% (volume by volume).…”
Section: Methodsmentioning
confidence: 99%